Dynamics of the postnoon auroral oval - McEwen, D. J.; Creutzberg, F. (Canadian Journal of Physics, 1986)
The morphology of the postnoon auroral oval (1300–1500 magnetic local time) as determined by ground-based optical observations with all-sky TV's and meridian scanners at Sachs Harbour, N.W.T., and Cape Parry, N.W.T., is described. Arcs associated with the "inverted-V" type of precipitation events, frequently observed with rocket and spacecraft particle detectors during this time period, are found to be short-lived, narrow, and sometimes of very restricted east–west extent. These arcs form the main feature of the auroral oval, which appears to be delineated almost ex0clusively by 6300-Å emission. The mechanism for their generation is consistent with local injections of magnetosheath plasma into the dayside boundary layer.